Produktivitas Induk Kambing Boerlok (Boer X Lokal) pada Berbagai Porsi Darah Kambing Boer - M. Ashari; Happy Poerwoto; Rina Andriati; Zaid Al Gifari; Ikwan Firhamsah (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2025)
This study was conducted to evaluate the productive and reproductive performance of Boerlok does at different proportions of Boer goat blood. The research was carried out in areas of Boer × Local goat crossbreeding development in Lombok. The study location was determined using purposive sampling based on the breed of goats raised. A total of 90 Boerlok does were randomly selected as samples, consisting of 30 F1 Boerlok does, 30 F2 Boerlok does, and 30 F3 Boerlok does. The observed variables included body weight, body length, withers height, chest girth, days open, service per conception, service period, and kidding interval. Productive and reproductive performance data were analyzed descriptively using the mean and standard deviation (arithmetic mean ± standard deviation) according to data categories. Differences in productive and reproductive performance among goat breeds were analyzed using the t-test. The proportion of Boer goat blood had a significant effect (P < 0.05) on the productive performance of Boerlok does; higher proportions of Boer blood resulted in higher productive performance. The proportion of Boer blood in Boerlok does had no significant effect (P > 0.05) on the onset of first estrus postpartum, service period, and service per conception, but had a significant effect (P < 0.05) on first mating postpartum, days open, and kidding interval